2017
DOI: 10.1007/s13300-017-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

IDegLira Versus Insulin Glargine U100: A Long-term Cost-effectiveness Analysis in the US Setting

Abstract: IntroductionTreatment with IDegLira has the potential to improve glycemic control in patients with type 2 diabetes mellitus (T2DM) without the weight gain and with a lower risk of hypoglycemia than with other therapies. The aim of the present analysis was to evaluate the long-term cost-effectiveness of IDegLira versus insulin glargine U100 with re-education and up-titration of the dose for treatment of patients with T2DM failing to achieve glycemic control on basal insulin in the US setting.MethodsData were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…These findings are consistent with other published health economic analyses of IDegLira. Cost‐effectiveness evaluations based on clinical trial data on IDegLira have shown that it is likely to improve clinical outcomes and be cost‐effective versus several comparator regimens (basal insulin, basal‐bolus insulin, and GLP‐1 receptor agonists in combination with insulin) in patients with type 2 diabetes in the United States, the Netherlands, the Czech Republic, Sweden, the United Kingdom and Spain . Comparable health economic outcomes from the present study based on real‐world evidence are reassuring, as they indicate that the benefits of IDegLira observed in RCTs translate to the real‐world setting, and that similar improvements in long‐term outcomes with IDegLira can be anticipated for patients in routine clinical practice.…”
Section: Discussionsupporting
confidence: 55%
“…These findings are consistent with other published health economic analyses of IDegLira. Cost‐effectiveness evaluations based on clinical trial data on IDegLira have shown that it is likely to improve clinical outcomes and be cost‐effective versus several comparator regimens (basal insulin, basal‐bolus insulin, and GLP‐1 receptor agonists in combination with insulin) in patients with type 2 diabetes in the United States, the Netherlands, the Czech Republic, Sweden, the United Kingdom and Spain . Comparable health economic outcomes from the present study based on real‐world evidence are reassuring, as they indicate that the benefits of IDegLira observed in RCTs translate to the real‐world setting, and that similar improvements in long‐term outcomes with IDegLira can be anticipated for patients in routine clinical practice.…”
Section: Discussionsupporting
confidence: 55%
“…13,24 There is no current uniform national or international consensus for the optimal treatment regimen in type 2 diabetes, including the intensification steps beyond monotherapy, the ideal combination when basal insulin is introduced, and the In contrast with long-term models of type 2 diabetes, rates of complications were not included, as they were not expected to vary over the short-term time horizon of the analysis. [44][45][46] Furthermore, glycaemic control, a key driver of rates of diabetes-related complications, was equivalent in both arms. However, rates of diabetes-related complications can also be influenced by blood pressure, BMI and serum lipid levels, and IDegLira was associated with improvements in all of these risk factors versus BBT in the DUAL VII trial.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast with long‐term models of type 2 diabetes, rates of complications were not included, as they were not expected to vary over the short‐term time horizon of the analysis 44, 45, 46. Furthermore, glycaemic control, a key driver of rates of diabetes‐related complications, was equivalent in both arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost effectiveness of treatment interventions is a key consideration when choosing therapies for people with T2D. Direct comparison of the acquisition costs of different therapies is insufficient to inform healthcare payer decision making as there are multiple factors to consider aside from achieving glycemic control, including the likelihood and burden of adverse events such as hypoglycemia and body weight gain, quality of life, and, importantly, the prognosis for diabetes-related micro-and macrovascular complications [74][75][76].…”
Section: Cost-effectiveness Analysis Of Idegliramentioning
confidence: 99%